Pengembangan Modul Pembelajaran Tematik Terpadu Berbasis Contextual Teaching And Learning Pada Peserta Didik Kelas IV di Sekolah Dasar - Wahyuni, Sisri (LP2M Universitas Adzkia, 2023)
This research is motivated by several problems, namely there is no availability of integrated thematic learning modules based on contextual teaching and learning (CTL), teachers lack of linking learning with problems that exist in students' daily lives, educators have provided guidebooks in the form of teaching materials but students students are less interested, the teaching materials are not many pictures, the teaching materials are dominated by colorless images, because the paper used is only newsprint and is packaged normally, the practice fields are limited, so students cannot maximize their answers to the exercises. This study aims to develop and validate a module based on contextual teaching and learning (CTL). The type of this research is R&D development research (Research and Development). The development model carried out is a 4D model consisting of the definition stage, the design stage, the development stage, and the dissemination stage. The results of the research on the development of an integrated thematic learning module based on contextual teaching and learning with three validators of Adzkia University lecturers and one teacher of 22 Mata Air State Elementary School were declared very valid. With the level of validity obtained at the module development stage, the percentage of design feasibility (92.5%) and language (85.7%) and material from lecturers (87.5%) and material from teachers (92.5%). and the practicality level of the teacher's contextual teaching and learning (CTL)-based module (93.75%) and the practicality of the five students' contextual teaching and learning (CTL)-based module is (95.30%) and the effectiveness of three students (Gicela 100%), (Lidya 98%), (Faizza 98%). So it proves that the module based on contextual teaching and learning in integrated thematic learning theme 8 sub-theme 1 is declared very valid and feasible to use.